2020
DOI: 10.1186/s12888-020-02501-7
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory treatment in patients’ homes in the Netherlands: what do mental health professionals think of this?

Abstract: Background: Compulsory treatment in patients' homes (CTH) will be introduced in the new Dutch mental health legislation. The aim of this study is to identify the opinions of mental health workers in the Netherlands on compulsory community treatment (CCT), and particularly on compulsory treatment in the patients' home. Methods: This is a mixed methods study, comprising a semi-structured interview and a survey. Forty mental health workers took part in the semi-structured interview about CCT and 20 of them, worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Maybe this is because medication is something that mental health workers can easily provide (in contrast to proper housing or daytime activities) and it has proven to be effective in improving certain symptoms of mental health disorders. However, in a study on the opinions of mental health workers, mental health workers stressed that treatment not only involves medication, but other factors were also essential, such as a good therapeutic relationship, proper housing and access to jobs or daytime activities ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maybe this is because medication is something that mental health workers can easily provide (in contrast to proper housing or daytime activities) and it has proven to be effective in improving certain symptoms of mental health disorders. However, in a study on the opinions of mental health workers, mental health workers stressed that treatment not only involves medication, but other factors were also essential, such as a good therapeutic relationship, proper housing and access to jobs or daytime activities ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with major depressive disorder (MDD) often cannot or will not come to an rTMS clinic for treatment, especially twice a day, which studies have shown is efficacious [ 10 ]. Hence, an emergent view from many mental health professionals is that a viable solution may be inexpensive, portable home-use rTMS devices, particularly as post-COVID demand for telemedicine and home treatment for mental health disorders has remained high [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. A recent German study found that 50% of people would prefer mental health treatment at home, and another 20% indicated preference for online therapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%